PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.2 SMP ISLAM AS-SHOFA PEKANBARU - Desfi Helvina; Rini Dian Anggraini; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims by the students’math achievement at class VII.2 SMP Islam As-Shofa pekanbaru, there are 9 students’ achieving passing grade for attitude aspect and for aspects of knowledge and skills 7 students’ or 35% on the main discussion about lines and angels. So there are 11 students who don’t achieve passing grade for attitude aspect and 13 students for aspects of knowledge and skills, it means that there are some students who don’t achieve passing grade (KKM ) from school. This research is aims to increase learning process and students’ math achievement at class VII.2 SMP Islam As-Shofa pekanbaru in rectangular and triangle, through the implentation cooperative learning model of structural Think Pair Square. The subject are 20 students from class VII.2 SMP Islam As-Shofa pekanbaru consist of 12 male and 8 famale students with the heterogenous level. The collecting of the data instruments are observation and math achivement test. The research finding is that there is students’ achievement that can be seen from the percentage of students’ achive passing grade (KKM) for attitude aspect with average is about 55%. The percentage of the score increase about 70% at the first daily test and the percentage of the score also increase about 85% at the second daily test. for aspects of knowledge with average is about 35%. The percentage of the score increase about 45% at the first daily test and the percentage of the score also increase about 70% at the second daily test. And for skills aspects with average is about 35%. The percentage of the score increase about 55% at the first daily test and the percentage of the score also increase about 85% at the second daily test Based on the previous result at can be concluded that the implentation of cooperative learning model of structural approach Think Pair Square to improve students’ math achievement at class VII.2 SMP Islam As-Shofa pekanbaru of rectangular and triangle on main topic of second semester 2014/2015.Key Word : Students’ math Achievement, Cooperative Learning Model Structural Approach of Think Pair Square, Classroom Action Research.